Pengaruh Pembiayaan dan Ukuran Perusahaan terhadap Profitabilitas (ROA) pada PT Bank Panin Dubai Syariah Tbk - Nasfizar Guspendri; Revi Candra (Jurnal Pasar Modal dan Bisnis, 2020)
The purpose of this study is to explain how much influence the financing and size of the company on profitability at PT Bank Panin Dubai Syariah Tbk. This type of research that I use is quantitative descriptive research that is at PT Bank Panin Dubai Syariah Tbk. The data source of this study uses data obtained from the Indonesia Stock Exchange and the Financial Services Authority (OJK) in the form of secondary data in the form of quarterly financial reports of PT Bank Panin Dubai Syariah Tbk. The data collection technique is documentation in the form of quarterly financial reports that are published. The data test used is the classical assumption analysis and goodness of fit with the F test. Data analysis uses multiple linear regression analysis, T-test, and the coefficient of determination test. Data processing using Statistical Product and Service Solution (SPSS) IBM version 22. The results of this study indicate that financing influences ROA, financing influences company size. Company size affects ROA. The size of the company in this study does not effectively act as an intermediary variable between the financing variables on ROA because the financing variable produces a negative coefficient on company size and the firm size variable also has a negative effect on ROA. It was concluded that H4 was rejected. The determinant coefficient shows that simultaneous financing and firm size influence ROA.